Characterization clinical, biochemical and molecular studies of a patient affected for niemann pick type B disease - Martínez, Lidia Dora (2015)
Fil: Martínez, Lidia Dora. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Centro de Estudio de las Metabolopatías Congénitas; Argentina.